A new Loureedia species on overgrazed former cork oak forest in Morocco (Araneae: Eresidae) - Gál, János; Kovács, Gábor; Bogyó, Richárd; Vári, Gábor; Prazsák, István (Animal Welfare, Etológia és Tartástechnológia (AWETH), 2016)
In this paper a new velvet spider species from Morocco is described from an overgrazed former cork oak [Quercus suber (Linné 1753)] forest. It is the second known species of the hitherto monotypic genus Loureedia. Loureedia maroccana sp. n. is distinguished from L. annulipes (Lucas, 1857) by the morphology of the conductor, the anteriorly widening cephalic region of the prosoma and opisthosoma decorated with a lobed, bright red marking on the dorsal side. Furthermore, three partial gene fragment sequences (histone 3, 28S ribosomal and cytochrome c oxidase) are also given, supporting the establishment of the new species.